Deciphering the Transcriptional Response Mediated by the Redox-Sensing System HbpS-SenS-SenR from Streptomycetes - Busche, Tobias; Winkler, Anika; Wedderhoff, Ina; Rückert, Christian; Kalinowski, Jörn; Ortiz de Orué Lucana, Darío (PLOS ONE, 2016)
The secreted protein HbpS, the membrane-embedded sensor kinase SenS and the cytoplasmic response regulator SenR from streptomycetes have been shown to form a novel type of signaling pathway. Based on structural biology as well as different biochemical and biophysical approaches, redox stress-based post-translational modifications in the three proteins were shown to modulate the activity of this signaling pathway. In this study, we show that the homologous system, named here HbpSc-SenSc-SenRc, from the model species Streptomyces coelicolor A3(2) provides this bacterium with an efficient defense mechanism under conditions of oxidative stress. Comparative analyses of the transcriptomes of the Streptomyces coelicolor A3(2) wild-type and the generated hbpSc-senSc-senRc mutant under native and oxidative-stressing conditions allowed to identify differentially expressed genes, whose products may enhance the anti-oxidative defense of the bacterium. Amongst others, the results show an up-regulated transcription of genes for biosynthesis of cysteine and vitamin B12, transport of methionine and vitamin B12, and DNA synthesis and repair. Simultaneously, transcription of genes for degradation of an anti-oxidant compound is down-regulated in a HbpSc-SenSc-SenRc-dependent manner. It appears that HbpSc-SenSc-SenRc controls the non-enzymatic response of Streptomyces coelicolor A3(2) to counteract the hazardous effects of oxidative stress. Binding of the response regulator SenRc to regulatory regions of some of the studied genes indicates that the regulation is direct. The results additionally suggest that HbpSc-SenSc-SenRc may act in concert with other regulatory modules such as a transcriptional regulator, a two-component system and the Streptomyces B12 riboswitch. The transcriptomics data, together with our previous in vitro results, enable a profound characterization of the HbpS-SenS-SenR system from streptomycetes. Since homologues to HbpS-SenS-SenR are widespread in different actinobacteria with ecological and medical relevance, the data presented here will serve as a basis to elucidate the biological role of these homologues.